Dry potato extracts improve water holding capacity, shelf life, and sensory characteristics of fresh and precooked beef patties1. (March 2019) - Colle, M.C.; Richard, R.P.; Smith, D.M.; Colle, M.J.; Loucks, W.I.; Gray, S.J.; Reynolds, Z.D.; Sutton, H.A.; Nasados, J.A.; Doumit, M.E.
Abstract: The objective was to examine shelf stability, cooked product yield, and sensory characteristics of beef patties that had no binder (Control), incorporated soy flour (Textured Vegetable Protein; TVP) or one of three dry potato extracts: X-TRATOS™ (potato extract), X-TRATOS™ O (potato extract with mustard), or X-TRATOS™ W (potato extract with sodium acid pyrophosphate). In retail display patties, all binders decreased discoloration and lipid oxidation compared to Control, and X-TRATOS™ O was superior ( P  < 0.05) to all other treatments. Cooking yield was higher ( P  < 0.05) in patties containing potato extracts compared with patties containing TVP, which had higher yield than Control patties. Beef patties with potato extracts were juicier ( P  < 0.05) than Control and TVP patties and had higher ( P  < 0.05) overall acceptability than Control patties. We conclude that potato extracts are effective binders for use in fresh or precooked beef patties because they improve retail shelf life, cooked product yield, and sensory characteristics.